Perfil clínico-epidemiológico e bacteriológico de otite externa em cães e avaliação da aplicação de prometazina como estratégia antibiofilme - Guedes, Rodrigo Fonseca de Medeiros (2024)
Otitis externa (OE) is an inflammation of the external ear canal with a complex and multifactorial etiology associated with predisposing, primary and perpetuating factors and secondary bacterial and fungal infections, which lead to recurrence of the disease. However, the treatment of otitis is challenging when analyzing the emergence of biofilm formation associated bacterial infections, a community of sessile bacteria immersed in a polymeric matrix with expression of efflux pumps. Considering the clinical, epidemiological and microbiological profile of otitis, the use of drugs that act on efflux pumps and biofilm is an alternative for the treatment of OE with recurrent bacterial infection. In this context, promethazine (PMZ) is a phenothiazine with reported antimicrobial and antibiofilm activity, as well as being an efflux pump inhibitor. Therefore, the aims of this study were to carry out a clinical-epidemiological and microbiological profile of dogs with recurrent OE and to evaluate the antimicrobial and antibiofilm activity of the topical antimicrobials gentamicin (GEN) and enrofloxacin (ENR), commercial otologic formulations (FO) containing gentamicin (FO GEN) or enrofloxacin (FO ENR), and PMZ against bacterial isolates obtained from dogs with OE, as well as the effect of PMZ on the dynamics of biofilm formation over 120 hours, as a proposal for long-term therapy. Therefore, 120 ears of 70 dogs with recurrent OE (50 bilateral and 20 unilateral otitis) were evaluated for the type of otitis (erythematous-ceruminous or suppurative), clinical parameters (erythema, hyperplasia, erosion/ulceration and exudate) and cytological parameters (cocci, bacilli, yeasts and neutrophils) by scores (0 to 4), bacterial isolation profile and antimicrobial sensitivity. The planktonic bacterial sensitivity to PMZ (12.2-6250 µg/mL), GEN (0.125-64 µg/mL), ENR, FO GEN and FO ENR (0.03-16 µg/mL) was evaluated to determine the minimum inhibitory concentrations (MIC), following the CLSI recommendations. The minimum biofilm eradication concentration (MBEC) was also determined by broth microdilution. To assess the effect on biofilm growth, PMZ was tested at three concentrations: MIC, MIC/2 and MIC/8, with daily readings at intervals of 48, 72, 96 and 120 hours. 174 bacteria were isolated, the most prevalent being Staphylococcus intermedius, Staphylococcus schleiferi, Proteus mirabilis and Pseudomonas aeruginosa, associated with varying clinical and cytological scores and antimicrobial sensitivity profiles. The MICs of PMZ and GEN, ENR and FO ranged from 48.83 to 781.25 µg/mL and 0.0625 to 64 µg/mL, respectively. The MICs of GEN, ENR and FO ranged from 1 to 256 µg/mL. PMZ significantly reduced (P<0.05) the biomass of mature biofilm, with BMSCs ranging from 48.8 to 6,250 µg/mL and reduced (P<0.01) biofilm formation for up to 120 hours, at concentrations corresponding to the MIC obtained against each isolate. It was concluded that erythematous-ceruminous had a higher clinical occurrence and the highest clinical and cytological scores were observed in suppurative otitis. PMZ was effective against the microorganisms associated with EO. The data suggest that PMZ is a promising antimicrobial and antibiofilm agent for the treatment and prevention of otitis externa with recurrent bacterial infection in dogs.